Household Fuel Use and Fuel Switching in Guatemala - World Bank (Washington, DC, 2014)
Household fuel choice in the past, has often been analyzed and understood through the lens of the energy ladder model. This model places relatively heavy emphasis on household fuel switching in response to rising incomes. This report views energy use through a household economics framework. The household economics framework clarifies that, in addition to income and market prices, the opportunity costs of firewood collection also need to be taken into account, in shaping demand for all fuels. The opportunity costs of firewood collection are determined by household cash, labor, land, and wood resources. Fuel choices therefore need to be understood in terms of relative household resource scarcities. The household economics framework also makes it clear that it may be perfectly rational for households to use a portfolio of different energy sources at any point in time. The results of logit, and multinomial logit regression analysis suggest that expenditure, education, household size, region, ethnicity, electrification status, and gender composition are important in influencing fuel choice. Prices and opportunity costs of firewood also matter. It remains intriguing that so many urban households continue to use wood, which is not a cheap fuel when it has to be purchased. Experience of household energy use in Guatemala suggests that, as household fuel policies elsewhere concerned with switching from biomass, need to look beyond simple pricing instruments to a wider array of policy options. Household energy strategies must be based on the realization that large groups will continue to meet their cooking needs with fuel wood for the foreseeable future. Strategies therefore cannot rely exclusively on inter-fuel substitution. A balance needs to be struck between policies aiming at inter-fuel substitution, and policies seeking to ameliorate the negative consequences of fuel wood, such as improved stoves and better ventilation. And, liquefied petroleum gas (LPG) needs to be targeted primarily to areas where households rely on expensive purchased wood.